Note on the effect of low temperatures on the survival of adults and larvae of the American black flour beetle, Tribolium audax - Barker, P.S. (Phytoprotection, 1991)
Flour infested with adults and late-instar larvae of the American black flour beetle, Tribolium audax, was held for 1, 2, 4, 8, 12, 17, 24, and 45 weeks at each of the following temperatures: -5, 3, and 10 °C, and for 1, 3, 5, 7, 8, 13, and 15 days at -15°C. Survival of the adults and larvae declined with increasing time of exposure at each temperature. Some adults and larvae survived 45 weeks at -5 and 10°C, but only larvae survived 45 weeks of exposure at 3°C. The LT50 and LT95 were determined for each temperature. No insects survived an exposure of 15 days at -15°C. Low temperatures are unlikely to be useful as a practical means for control of T. audax.